Representasi Kota Balikpapan dan Kota Samarinda dalam Cerpen (Hidup) Matinya Sebuah Kota Karya Raudal Tanjung Banua: Representation of Balikpapan and Samarinda in “(Hidup) Matinya Sebuah Kota” Short Story by Raudal Tanjung Banua - Sugiarto, Septian Rifki (Journal of Literature and Education, 2024)
Cities and literature have a very close relationship. It can be seen from the number of cities that are the primary inspiration for authors in creating literary works. One literary work that tells the story of a city is the short story (Hidup) Matinya Sebuah Kota by Raudal Tanjung Banua. As the title suggests, this short story tells a lot about the state of cities worldwide and in Indonesia. Two of the many cities in East Kalimantan are described in the short story: Balikpapan and Samarinda City. This research discusses the description of the two cities represented in the short story. This research uses representation theory with interpretation analysis as the data analysis technique. The result of this research is that the short story shows that Samarinda is facing various problems, such as an increasingly crowded environment and being vulnerable to floods. On the other hand, Balikpapan is depicted as a city that is developing in an organized and reasonable way. It has caused Balikpapan to become the administrative center, replacing the role of Samarinda. All of this is evidence that the dynamics of the development of cities are only sometimes stable and can change or be replaced over time.